2021
DOI: 10.3390/min11050454
|View full text |Cite
|
Sign up to set email alerts
|

EMPA, XRD, and Raman Characterization of Ag-Bearing Djurleite from the Lubin Mine, Lower Silesia, Poland

Abstract: The chalcocite group minerals are widely distributed among different hydrothermally affected rocks, the oxidized zone of copper sulfide deposits, or may be even crystalline from supersaturated volcanic gases. Some of the chalcocite group minerals form the main Cu orebodies. Djurleite (Cu31S16) is a rare member of the chalcocite group, with a very complex structure. The physical and chemical similarities between all members of the group make them almost unidentifiable by macroscopic and microscopic methods. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
(42 reference statements)
0
3
0
Order By: Relevance
“…The GIXRD spectrum of position 17 details a small shift of several peaks to lower 2θ values, which is characteristic of the increase of Cu concentration for these copper sulfide compounds [39,42], and a general decrease of peak intensity, thus indicating reduced crystallinity. Nevertheless, the main phase is still considered to be Cu 31 S 16 [42,43].…”
Section: Morphological and Structural Assessmentmentioning
confidence: 98%
See 1 more Smart Citation
“…The GIXRD spectrum of position 17 details a small shift of several peaks to lower 2θ values, which is characteristic of the increase of Cu concentration for these copper sulfide compounds [39,42], and a general decrease of peak intensity, thus indicating reduced crystallinity. Nevertheless, the main phase is still considered to be Cu 31 S 16 [42,43].…”
Section: Morphological and Structural Assessmentmentioning
confidence: 98%
“…The GIXRD spectrum of position 17 details a small shift of several peaks to lower 2θ values, which is characteristic of the increase of Cu concentration for these copper sulfide compounds [39,42], and a general decrease of peak intensity, thus indicating reduced crystallinity. Nevertheless, the main phase is still considered to be Cu 31 S 16 [42,43]. Moreover, the GIXRD spectrum of position 18 (furthest from the As-S target), shown in Figure S4d in SM, presents no peaks, revealing the complete amorphization of the film.…”
Section: Morphological and Structural Assessmentmentioning
confidence: 98%
“…40 A detailed literature survey revealed that the djurleite phase is only stable up to 95 ± 3 °C at atmospheric pressure. [41][42][43] Thus, the primary reason behind its formation via SSP 2 is the lower than boiling water decomposition temperature of the complex in OAm. However, an explanation was still required regarding the ultralow decomposition temperature of 2 compared to 1.…”
Section: Preparation and Characterization Of Copper Sulde Nanomaterialsmentioning
confidence: 99%